A STUDY ON JOB SATISFACTION AMONG EMPLOYESS TOWARDS WORK FROM HOME AT WEALTH INDIA FINANCIAL SERVICE PVT LTD - A. , Devendran; R, Bharathvajan; S , V Elumalaiyan (International Journal of Psychosocial Rehabilitation, 2020)
In today’s world, most graduates are not having the job because of the job dissatisfaction unless and until people get satisfied with the job, the role of job satisfaction is not effectively done in the organization. So the organization has taken some preventive measures to retain the employee, as well as being too satisfied with the job description. Job satisfaction helps to reduce the conflicts and retention strategy easily implemented with the use of job satisfaction. The study was conducted at Wealth India Financial Services in Chennai; the sample taken from the company was 50. In this article, bring out meaning of job satisfaction and also how it change the attitude of an employee in the organization